Validation of a scale to assess adherence to oral chemotherapy based on the experiences of patients and healthcare professionals (EXPAD-ANEO) - Talens, Amparo; LÓpez-Pintor, Elsa; Guilabert, Mercedes; Cantó-Sancho, Natalia; Aznar, María Teresa; Lumbreras, Blanca (Frontiers in Pharmacology, 2023)
Background: Lack of adherence to Oral antineoplastic agents (OAAs) treatment has important clinical, social and economic consequences. Objective: To develop and validate a novel instrument for assessing adherence to OAAs, based on the reported experiences of people with cancer in relation to their treatment and the opinions of the healthcare professionals who care for them. Methods: We performed a multicenter validation study of a scale designed to assess adherence to OAAs. First, a steering committee developed the items for an initial scale, based on the results of a qualitative study that evaluated patients’ and professionals’ experiences with this treatment. We then assessed the validity and reliability of the initial scale in a sample of 268 outpatients with cancer who received their OAAs from four Spanish hospitals. Results: The mean age of the sample of 268 outpatients was 64.1 (standard deviation [SD] 12.4) years, and 47% of participants were women. With the results of this analysis, we developed the EXPAD-ANEO scale, which has 2 factors, one for beliefs and expectations and another for behavior. Both factors explain 52% of the explained common variance. Good reliability was obtained, with a McDonald’s omega of 0.7 for the first factor and 0.6 for the second factor. The fit indices were optimal (Root Mean Square Error of Approximation = 0.02, Comparative Fit Index = 0.99, Tucker Lexis Index = 0.99 and Standardized Root Mean Squared Residual = 0.03), which verifies the appropriateness of the items to the model. We measured EXPAD-ANEO criterion validity against pill count, obtaining a specificity of 80%. We measured convergent validity with the Morisky-Green test and found a significant association (p < 0.001). We measured divergent validity with questions on health literacy from the 16-item European Health Literacy Survey and found no correlation (p = 0.153). Conclusion: EXPAD-ANEO is the first validated instrument for evaluating patients’ experiences with and adherence to OAAs, providing valuable information that can help health professionals to establish individual strategies or collective programs for improving therapeutic results and reducing healthcare costs.